Strategies of the control of an outbreak of leptospiral infection in dairy cattle in Northeastern Brazil - Pimenta, Carla Lauise Rodrigues Menezes; da Costa, Diego Figueiredo; Silva, Maria Luana Cristiny Rodrigues; Pereira, Hélio Domingos; Júnior, João Pessoa Araújo [UNESP]; Malossi, Camila Dantas [UNESP]; Ullmann, Leila Sabrina [UNESP]; Alves, Clebert José; de Azevedo, Sérgio Santos (Springer Nature, 2018)
The aim of the present study was to describe the strategies of the control of an outbreak of leptospiral infection in dairy cattle in Maranhão State, Northeastern Brazil. In the period from January to July 2015, 18 (17%) out of 106 cows presented abortion, six (5.7%) stillbirth, and 12 (11.3%) repeated estrus, totaling 24 animals with reproductive problems. The diagnosis of leptospirosis was based on serology (microscopic agglutination test—MAT), bacteriological culture, and polymerase chain reaction (PCR). Antibiotic therapy, vaccination protocols, and changes in management practices were suggested as control measures. Of all animals on the farm (n = 280), 136 (48.6%) were seropositive for at least one serovar of Leptospira sp. No pure leptospiral culture was obtained. Eight of the animals with reproductive problems yielded positive PCR results (vaginal fluid of seven animals and urine and vaginal fluid of one animal). Genetic sequencing of a vaginal fluid/urine PCR-positive sample revealed Leptospira borgpetersenii. One year after the adoption of control measures, no reproductive problems were observed. Thus, leptospirosis probably caused the reproductive failures in the herd, and the control and prevention measures implemented were efficient in controlling the disease.
Keywords: Control; Leptospira sp.; Outbreak; Reproductive failures